The Effect of Virtual Hotel Tours on The Speaking Skills of Eleventh Grade Students in The Hospitality Department at SMK PGRI 1 Giri Banyuwangi in The 2024/2025 Academic Year - Rachel Ayundi Tata Riski; Miftah Ayufiyanda Anggraini; Nur Alvy Sahrin; Najwa Aprilianti Susanto; Wageyono (MAN Insan Cendekia Jambi, 2025)
Speaking is a crucial component of language proficiency that supports students' communication skills, particularly in vocational contexts such as hospitality. This study was conducted to examine the effect of Virtual Hotel Tours on the speaking skills of eleventh-grade students in the Hospitality Department at SMK PGRI 1 Giri Banyuwangi during the 2024/2025 academic year. A pre-experimental design with a one-group pretest- posttest approach was employed. The participants consisted of 36 students from the eleventh-grade Hospitality class. Data were collected using a speaking performance test based on five aspects: pronunciation, grammar, vocabulary, fluency, and comprehension, and analyzed using SPSS version 27. The results showed a significant improvement in speaking scores, with the mean score increasing from 56.78 in the pre-test to 73.89 in the post-test. The Paired Sample T-Test revealed a t-value of 38.919, which exceeded the t- table value of 2.030, with a significance level below 0.05, indicating a statistically significant difference. These findings suggest that the use of Virtual Hotel Tours had effect on students’ speaking skills, particularly in the aspects of fluency, pronunciation, grammar, vocabulary, and comprehension, with pronunciation showing the highest improvement compared to the other aspects.